1984
DOI: 10.1136/jcp.37.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of an epitope of the transferrin receptor in human cervical epithelium--a potentially useful cell marker.

Abstract: SUMMARYThe distribution of an epitope of the transferrin receptor in the human uterine cervical epithelium has been investigated. Immunohistochemical staining, both immunofluorescent and immunoperoxidase, was performed on biopsy specimens and cytological samples from normal, dysplastic, and neoplastic cervical epithelia using the monoclonal OKT9 antibody. The results of staining 145 cervical biopsy specimens with OKT9 showed widespread staining in all malignant epithelia and most severely dysplastic epithelia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 14 publications
(1 reference statement)
1
16
0
Order By: Relevance
“…2A). The increased level of transferrin receptor in vitro correlates with in vivo data showing increased transferrin receptors in high-grade cervical lesions and cancers as measured by immunohistochemistry (14)(15)(16). Thus, the increase in transferrin receptors is not an artifact of in vitro culturing of the cells.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…2A). The increased level of transferrin receptor in vitro correlates with in vivo data showing increased transferrin receptors in high-grade cervical lesions and cancers as measured by immunohistochemistry (14)(15)(16). Thus, the increase in transferrin receptors is not an artifact of in vitro culturing of the cells.…”
Section: Resultssupporting
confidence: 61%
“…In a subsequent study, the cervical cancer cell line HeLa was also shown to be sensitive to DHA although a mechanism for cell death was not elucidated (8). We speculated that both cervical cancer and immortalized cell lines, which are sensitized to apoptotic cell death by the expression of the E6 and E7 oncogenes (9-13) and overexpress the transferrin receptor (14)(15)(16), might be killed by these antimalarial compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that the content of receptors specific for transferrin in various cancerous tissues including the lung, stomach, colon and breast is substantially greater than that of normal conterpart. Lloyd et al (1984) have described that only a small amount of Tf • R was observed either in normal of dysplastic epithelia of uterine cervical biopsy specimens by immunohistochemical study. We have found that the amount of Tf.…”
Section: Discussionmentioning
confidence: 99%
“…25,55 Because of the pivotal role of TfR in Fe uptake, the TfR is more abundantly expressed in rapidly dividing cells than quiescent cells, 56,57 and high levels of TfR expression have been identified on many tumors. [58][59][60] In fact, studies have shown that expression of TfR is more abundant in breast cancer tissue than in normal tissue. 60,61 Given the facts that estrogen and Fe exert their biological effects through their receptors, 62,63 it is important to know whether E2 affects TfR in cells with different ER and PR status.…”
Section: Discussionmentioning
confidence: 99%